2011
DOI: 10.1186/1472-6963-11-93
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of different models of home and community care services for older persons

Abstract: BackgroundCosts and consumer preference have led to a shift from the long-term institutional care of aged older people to home and community based care. The aim of this review is to evaluate the outcomes of case managed, integrated or consumer directed home and community care services for older persons, including those with dementia.MethodsA systematic review was conducted of non-medical home and community care services for frail older persons. MEDLINE, PsycINFO, CINAHL, AgeLine, Scopus and PubMed were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
215
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(229 citation statements)
references
References 42 publications
5
215
2
7
Order By: Relevance
“…50 Indeed, it is important to note that although this study found that high-integration teams cost more than other team types, in effect this simply means they provided more resources, which could arguably be viewed as a positive outcome itself. These findings are in keeping with the systematic review mentioned above 266 and might tend to suggest that more integrated teams are better at accessing and/or targeting resources for a particular subsection of their caseload with less obvious dependency, perhaps with a view to maintaining their independence. Such provision would fit well with concerns about the concentration of resources on people with high-level needs, at the expense of those for whom relatively small inputs might prevent or delay deterioration.…”
Section: Broader Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…50 Indeed, it is important to note that although this study found that high-integration teams cost more than other team types, in effect this simply means they provided more resources, which could arguably be viewed as a positive outcome itself. These findings are in keeping with the systematic review mentioned above 266 and might tend to suggest that more integrated teams are better at accessing and/or targeting resources for a particular subsection of their caseload with less obvious dependency, perhaps with a view to maintaining their independence. Such provision would fit well with concerns about the concentration of resources on people with high-level needs, at the expense of those for whom relatively small inputs might prevent or delay deterioration.…”
Section: Broader Implicationssupporting
confidence: 83%
“…On the other hand, a systematic review of home and community services for frail older people, including people with dementia, concluded that although evidence from non-randomised trials showed integrated care increased service use, evidence from randomised trials indicated it did not improve clinical outcomes. 266 A major difficulty with this literature is that the term integration is not always defined, yet appears to have taken on a wide range of meanings ranging from the closer co-ordination of an individual's clinical care to the formation of joint health and social care organisations. 257,262 This has reflected the fact that integration can take place at different levels in the care system from performance of care tasks to care systems.…”
Section: Discussionmentioning
confidence: 99%
“…The review found that consumer-directed care increased satisfaction and use of community services but not outcomes; and that integrating care across health and social boundaries did not lead to explicit benefits (Low, 2011). These findings add to evidence that the appointment of dementia specialists and attention to case management in the community (not just the provision of training or the integration of services) can produce positive outcomes.…”
Section: Interventions For People With Dementia Living In the Communitymentioning
confidence: 88%
“…Many studies aiming at evaluating present experiences of case management for people with dementia have found evidence in favour of the method unclear and contested, partly because of the multiplicity of case management forms in use (Low, Yap, & Brodaty, 2011).…”
Section: Translation Of the Case Management Methodsmentioning
confidence: 99%